Biotechnological and virological analysis of canine parvovirus infections by C-reactive protein levels, serological, hematological and molecular techniques: Biotechnological analysis of canine parvovirus infections - Palanci, Pinar; Tekelioglu, Bilge Kaan (Cellular and Molecular Biology, 2023)
The study aims to approach Canine Parvovirus (CPV) diagnosis using multi-method biotechnological techniques including molecular, serological, and hematological analyses. CPVs are causing severe global viral diseases with high dog mortality. Samples were taken from 52 unvaccinated dogs exhibiting symptoms between 2020 and 2021. These included stool, blood, serum, and patient data. CPV genomic DNA was extracted from fresh stools, with DNA concentration and purity measured using Nano drop-spectrophotometry. CPV genomic DNA was detected via RT-PCR in 29 samples (55.8%), CPV IgM-Ab and IgG-Ab were detected in the sera through ELISA in 27 samples (51.9%), and Canine parvovirus antigens were identified in the stool samples by immunochromatography in 20 samples (38.5%). Utilizing canine-specific quantitative ELISA kits, the average level of serum C-reactive protein (CRP) was determined to be 4.66 g/L (with a range of 3.27 to 6.05 g/L). Hematological analysis revealed lymphopenia in 89.6%, leucopenia in 44.8%, anemia in 68.9%, and low hematocrit in 82.8%. All the dogs examined were under 1 year of age, among which 21 (72.4%) were up to 3 months old, and 8 (27.6%) were up to 6 months old, testing positive for CPV. The highest CPV positivity, at 93.1% (n=27), was observed among dogs with outdoor access. The results indicated that hematological parameters and CRP alone were not specific for CPV diagnosis, but provided valuable data for prognosis and differential diagnosis. No significant differences were observed in RT-PCR and ELISA results. However, a noticeable reduction in positivity rates was evident in lateral immunochromatographic viral antigen detection in stool.